Searching for profit-shifting in China - Xuefeng Qian; Bifei Tian; W. Robert Reed; Ziruo Chen (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
This paper investigates profit-shifting behaviour among multinational corporations (MNCs) in China. The authors exploit the flat-rate structure of China's corporate income tax, along with its system of targeted, preferential rates, to estimate the relationship between profits and tax rates. Their sample consists of approximately 60,000 observations of foreign-owned MNCs from the years 2005-2009. Using the traditional approach of regressing before-tax profits on tax rates, the authors find evidence consistent with profit-shifting. However, this approach is suspect because the nature of China's tax preferences makes it especially vulnerable to omitted variable bias. Accordingly, the authors employ finite mixture modelling to search for the existence of a group of profit-shifting MNCs. While their analysis identifies two types of firms, subsequent investigation failed to produce any evidence linking these to profit-shifting behavior. Robustness checks exploiting the panel nature of the dataset, along with further investigation of investment-tax elasticities, confirm the authors' null finding of profit-shifting. One reason for the lack of profit-shifting among Chinese MNCs may be that corporate tax rates were relatively low during this period.
Keywords: F23; H32; 330; multinational corporations (MNCs); profit shifting; tax elasticity; finite mixture model; China